Investigation of simultaneous thermal oxidation and nitridation of sputtered zirconium on silicon and silicon carbide in nitrous oxide gas environment - Wong, Yew Hoong (2012)
Thin film Zr on Si and SiC were formed by sputtering. The films then underwent simultaneous oxidation and nitridation in N2O. The effects of oxidation/nitridation durations (5 20 min) and temperatures (500 1100oC) on the sputtered Zr/Si system and the effects of oxidation/nitridation temperatures (400 900oC) and the concentrations of N2O (10 100%) to the characteristics of the sputtered Zr/SiC system were studied. Structural, chemical, and electrical properties of the samples were examined. X-ray photoelectron spectroscopy results showed that ZrO2 thin film was formed with an interfacial layer (IL) of Zr-silicate oxynitride (ZrSiON) on Si, while Zr-oxynitride (ZrON) thin film was formed with an IL of ZrSiON and carbon nitride on SiC.